Determinants of Female Leaders’ Careers in the Public Sector: The Moderating Role of Work-Life Balance - Suryatni, Mukmin; Nurmayanti, Siti; Hailuddin, Hailuddin; Husnan, Lalu Hamdani; Endri, Endri; Sariwulan, Rd Tuty; Ridlo, Muhammad (International Review of Management and Marketing, 2024)
This study aims to determine the determinant factors that influence the career of female leaders. The determinant factors in question are divided into internal factors, namely self-efficacy and emotional intelligence, while external factors include social support and work-life balance. This study involved 150 respondents, and the criteria were female employees with echelon II, III, and IV positions in SKPDs within the scope of the NTB Provincial government. The data collection technique was a questionnaire analyzed using the Smart-PLS application. The results of this study indicate that self-efficacy, emotional intelligence, and work-life balance have a positive and significant effect on women's career maturity. Work-life balance can only moderate the influence of self-efficacy on women's career maturity. However, work-life balance has not been able to moderate the impact of emotional intelligence on career maturity, and it does not moderate the influence of social support on women's career maturity.